Acute Calcific Tendinitis of the Gluteus Medius - Berke Aras; Serdar Kesikburun; Ümüt Güzelküçük; Evren Yaşar; A. Kenan Tan (Türk Osteoporoz Dergisi)

(untitled)
Calcific tendinitis is an inflammatory condition occurring in numerous anatomic locations. Involvement of the gluteus medius tendon is uncommon. In this case we report a patient with hip pain due to calcific tendinitis of the gluteus medius tendon. A 39-year-old male patient was admitted to our outpatient clinic with a complaint of severe right hip pain, which persisted for two weeks and exacerbated with activity. Physical examination revealed marked tenderness around the right greater trochanter. On magnetic resonance imaging, inflammatory edematous changes were demonstrated in the region of the greater trochanter insertion of the gluteus medius tendon. Non-steroidal antiinflammatory drug was started to the patient by the diagnosis of acute calcific tendinitis. The patient reported no reduction in pain one week after the drug therapy. Thereafter, a corticosteroid injection to the lesion site was administered and patient’s symptoms decreased within three days. Clinicians should keep in mind the calcific tendinitis of the gluteus medius muscle in the differential diagnosis of hip pain. The diagnosis is made by physical examination and radiological findings of calcific deposits in the related tendon.